2019
DOI: 10.1371/journal.pone.0215803
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised, double-blind pilot and feasibility trial of an active behavioural physiotherapy intervention for acute whiplash-associated disorder (WAD)II

Abstract: Whiplash-associated disorder (WAD) causes substantial social and economic burden, with ≥70% patients classified as WADII (neck complaint and musculoskeletal sign(s)). Effective management in the acute stage is required to prevent development of chronicity; an issue for 60% of patients. An Active Behavioural Physiotherapy Intervention (ABPI) was developed to address both physical and psychological components of WAD. The ABPI is a novel complex intervention designed through a rigorous sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 101 publications
0
38
0
Order By: Relevance
“…The trial is designed by a team of researchers using a part of the results from the previous pilot and feasibility trial, in which a patient was a member of the trial steering committee 30 32. A patient will be planned to involve in this trial as a member of the trial management group.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The trial is designed by a team of researchers using a part of the results from the previous pilot and feasibility trial, in which a patient was a member of the trial steering committee 30 32. A patient will be planned to involve in this trial as a member of the trial management group.…”
Section: Discussionmentioning
confidence: 99%
“…Although whiplash-associated disorders (WAD) and non-specific neck pain can be different in the mechanism of injury and severity, their conditions and clinical characteristics are similar 24–27. An active behavioural physiotherapy intervention (ABPI) may, therefore, be useful in managing patients with non-specific neck pain based on the findings of the previous Acute Whiplash Injury Study (AWIS) pilot and feasibility trial 28–32. The findings demonstrated that 95% of the patients who received the ABPI fully recovered at 3 months follow-up, whereas approximately 17% of the patients who received standard physiotherapy fully recovered using a cut-off on the Neck Disability Index (NDI) ≤4 30–32.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations